The Influence of the Design Features of the Submersible Pump Rotor on the Vibration Reliability - Makivskyi O.; Kondus V.; Pitel J.; Sotnyk M.; Andrusiak V.; Polkovnychenko V.; Musthai M. (Журнал інженерних наук)
Pumping equipment consumes about 20 % of the electrical energy produced by humankind. A significant, even drastic, reduction in the weight and size indicators of pumping equipment leads to a decrease in the cost price and, therefore, competitiveness of such products in the market. Simultaneously, it makes it possible to use more valuable and high-quality construction materials and technologies that improve the reliability of equipment and its energy efficiency, which in turn is a clear step in solving many UN Sustainable Development Goals (SDGs). According to the research results, it was proved that by increasing the frequency of the drive, it is possible to reduce the mass and size indicators of the submersible pump for the needs of the critical infrastructure sector by reducing the number of stages. Mainly, the amplitudes of oscillations near the rotation frequency are 12–22 % and do not exceed 35 % of the gaps in the seals, as required by the available international standards to ensure the guaranteed vibration reliability of the pump. Overall, using a bearingless support design will significantly increase the reliability of the developed pump.